OPERATING MANAGEMENT OF CENTRAL VENOUS HYPERTENSION COMPLICATING UPPER EXTREMITY DIALYSIS ACCESS - Bachleda, Petr; Utikal, Petr; Kalinova, Lucie; Drac, Petr; Zadrazil, Josef; Koecher, Martin; Cerna, Marie (Biomedical papers, 2008)
Aim: To evaluate the importance of surgical bypass between the terminal part of functional arteriovenous shunt (av) for hemodialysis on upper extremity and inner jugular vein in axillosubclavian venous segment obstruction associated with central venous hypertension.Method: Retrospective assessment of surgical bypass between central segments of av fistula and ipsilateral/contralateral inner jugular vein using ePTFE graft in 17 patients over a 20 year period (1987-2006).Results: The surgical procedure was not associated with intra- or post-operative complications. Primary cumulative bypass and av fistula function persisted for 26 months on average.Conclusion: An accurate bypass to salvage the functional dialysis access associated with central venous hypertension requires careful decision based on clinical and radiological examination. The bypass procedure is beneficial where endovascular treatment is not indicated. Clinical and radiological bypass monitoring is crucial.
Keywords: Hemodialysis arteriovenous fi stula/Central venous hypertension/Av fi stula - internal jugular vein bypass